School Branding Strategy for The Tahfidzul Qur'an Program in Moral Education in West Sumatra - Noviyani, Rafiqa (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
The purpose of this research is to explore the implementation of the tahfidz program branding in moral guidance. Qualitative research involved case study designs at six secondary schools in West Sumatra, namely SMPIT Cahaya Makkah, SMPIT Al-Kahfi, SMPIT Madinah Al-Kahfi, TQIT Sahabat Cendikia Pariaman, SMPIT Ar-Risalah, and SMPIT Adzkia. These schools were selected through purposive sampling using non-random techniques based on specific characteristics relevant to the research. Data were collected through participatory observation, documentation, and interviews, enabling an in-depth exploration of school branding based on the Tahfidz program implemented in the target schools. The results of the study show that branding tahfidz program in schools contributes significantly to fostering students' morals and creates a positive image in the community. The school branding strategy begins with strengthening the paradigm of tahfidz and morals, reinforced by the concepts of intention and responsibility, and utilizing the media for branding marketing. The methods and models of moral-based tahfidz learning are derived from the school's objectives, vision, mission, and curriculum, as well as from a means of internalizing and evaluating moral values.